Quantitation of lysosomal trapping of basic lipophilic compounds using in vitro sssays and in vilico predictions based on the determination of the full pH profile of the endo-/lysosomal system in rat hepatocytes - Schmitt, Maximilian V.; Fricker, Gert (Drug metabolism and disposition, 2019)
Lysosomal sequestration may affect the pharmacokinetics, efficacy, and safety of new basic lipophilic drug candidates potentially impacting their intracellular concentrations and tissue distribution. It may also be involved in drug-drug interactions, drug resistance, and phospholipidosis. However, currently there are no assays to evaluate the lysosomotropic behavior of compounds in a setting fully meeting the needs of drug discovery. We have, therefore, integrated a set of methods to reliably rank order, quantify, and calculate the extent of lysosomal sequestration in rat hepatocytes. An indirect fluorescence-based assay monitors the displacement of the fluorescence probe LysoTracker Red by test compounds. Using a lysosomal-specific evaluation algorithm allows one to generate IC50 values at lower than previously reported concentrations. The concentration range directly agrees with the concentration dependency of the lysosomal drug content itself directly quantified by liquid chromatography-tandem mass spectrometry and thus permits a quantitative link between the indirect and the direct trapping assay. Furthermore, we have determined the full pH profile and corresponding volume fractions of the endo-/lysosomal system in plated rat hepatocytes, enabling a more accurate in silico prediction of the extent of lysosomal trapping based only on pKa values as input, allowing early predictions even prior to chemical synthesis. The concentration dependency—i.e., the saturability of the trapping—can then be determined by the IC50 values generated in vitro. Thereby, a more quantitative assessment of the susceptibility of basic lipophilic compounds for lysosomal trapping is possible.